1966
DOI: 10.1063/1.1708211
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Dislocations in Ammonium Dihydrogen Phosphate: Production of Dislocation-Free Crystals

Abstract: The results of etch-pit and diffraction topographic studies on ammonium dihydrogen phosphate (ADP) are reported. These studies were carried out on specimens sectioned by abrasive wheel and string-saw from large single crystals grown from aqueous solution. The two characterization methods are shown to be in approximate one-to-one correspondence in the case of sections produced by abrasive sawing. Absence of both etch pits and topographic images in sections made by string-sawing of material well removed from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1970
1970
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Diffraction of X-rays in Bragg and Laue geometries by flat perfect crystals is well understood (Zachariasen, 1945;James, 1963;Hirsch & Ramachandran, 1950;Cole & Stemple, 1962;Batterman & Cole, 1964) and has been studied and tested in crystals where these assumptions hold to a good first approximation (K/illne & Aberg, 1975;Bearden, Marzolf & Thomsen, 1968;Deslattes, Torgeson, Paretzkin & Horton, 1966).…”
Section: Introductionmentioning
confidence: 99%
“…Diffraction of X-rays in Bragg and Laue geometries by flat perfect crystals is well understood (Zachariasen, 1945;James, 1963;Hirsch & Ramachandran, 1950;Cole & Stemple, 1962;Batterman & Cole, 1964) and has been studied and tested in crystals where these assumptions hold to a good first approximation (K/illne & Aberg, 1975;Bearden, Marzolf & Thomsen, 1968;Deslattes, Torgeson, Paretzkin & Horton, 1966).…”
Section: Introductionmentioning
confidence: 99%
“…They were proposed more than 30 years ago for nonlinear optical applications [see for instance Moritani et al (1983)]. Their structural characterization, performed by X-ray topography, has confirmed that the crystals are characterized by high crystal perfection (Deslattes et al, 1966;Bhagavannarayana et al, 2006;Bhat et al, 1983), nearly dislocation free and free of inclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly little work has been carried out in this area, although the isomorphous solid, potassium dihydrogen orthophosphate has been well examined. In the few studies which have been made, X-ray topographic techniques have been used to define the propagation of dislocations during growth kinetic examinations (Chernov, Smol'skii, Parvov, Kuznetzov & Rozhanski, 1979) or to assess the quality of the grown crystals (Yoshimatsu, 1966;Deslattes, Torgesen, Paretzkin & Horton, 1966;Lefaucheux, Robert & Manghi, 1982), rather than to define the defect structure. In an attempt to rectify this situation and to resolve the question of growth on the pyramidal faces, we have attempted a comprehensive examination of the dislocation structure of ADP crystals prepared in a variety of manners, the mechan-ical properties of the solid and the influence of growth and mechanically induced dislocations and impurities on growth kinetics.…”
Section: Introductionmentioning
confidence: 99%